Exceptional Air Mass Transport and Dynamical Drivers of an Extreme Wintertime Arctic Warm Event. Issue 23 (11th December 2017) - Binder, Hanin; Boettcher, Maxi; Grams, Christian M.; Joos, Hanna; Pfahl, Stephan; Wernli, Heini
Abstract: At the turn of the years 2015/2016, maximum surface temperature in the Arctic reached record‐high values, exceeding the melting point, which led to a strong reduction of the Arctic sea ice extent in the middle of the cold season. Here we show, using a Lagrangian method, that a combination of very different airstreams contributed to this event: (i) warm low‐level air of subtropical origin, (ii) initially cold low‐level air of polar origin heated by surface fluxes, and (iii) strongly descending air heated by adiabatic compression. The poleward transport of these warm airstreams occurred along an intense low‐level jet between a series of cyclones and a quasi‐stationary anticyclone. The complex 3‐D configuration that enabled this transport was facilitated by continuous warm conveyor belt ascent into the upper part of the anticyclone. This study emphasizes the combined role of multiple transport processes and transient synoptic‐scale dynamics for establishing an extreme Arctic warm event. Key Points: A complex chain of extraordinary dynamical and physical processes resulted in an extreme wintertime Arctic warm event The warm air came from three different regions and experienced fundamentally different temperature evolutions before arriving in the Arctic Latent heating in ascending airstreams contributed to the setup of an unusual weather pattern that allowed the warm air to reach the Arctic